APPROXIMATION MODELS THE FORMATION PRESSURE ACCORDING TO GAS-DYNAMICS SURVEYS OF WELLS - Vladimir A. Tolpaev; Roman A. Ryskalenko (Вестник Северо-Кавказского федерального университета)
A convenient practical method for approximating of the formation pressure at an arbitrary point inside the reservoir is offered. The method uses measurements in neighboring wells which, unlike the classical methods of Lagrange and Newton, does not require linear axes of spatial interpolation.